Penerapan Metode Continuous Review pada Pusat Oleh-Oleh Keripik Rumah Adat Minang - Putri Khairiah Nasution; Nella Oktavia Rani Br Sirait (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2023)
Pusat Oleh-Oleh Keripik Rumah Adat Minang is a business engaged in the production of sweet potato chips, and selling various types of snacks, this business is located in Medan City, North Sumatra. This study aims to compare the total inventory costs of the company's policies and the Continuous Review method and determine the optimal order size. The data obtained is inventory data for 5 types of snacks in 2021. The method used is the continuous review method, based on the results of calculations for 5 types of snacks, the total inventory cost according to company policy is Rp.792,631,977/year, while the total inventory cost using the continuous review method is Rp.773.799,089/year. The results showed that the continuous review method has an optimal total inventory cost, so the company can save on expenses of Rp. 18,832,888 or 2,37% for 5 types of snacks. To facilitate the calculation in this study was conducted using the help of MATLAB software.